2016
DOI: 10.12659/msm.897150
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Mismatch Repair Proteins in Early and Advanced Gastric Cancer in Poland

Abstract: BackgroundMutations in DNA of mismatch repair (MMR) genes result in failure to repair errors that occur during DNA replication in microsatellites, resulting in accumulation of frameshift mutations in these genes and leading to DNA mismatch replication errors and microsatellite instability. Gastric cancers (GCs) with high MSI (MSI-H) are a well-defined subset of carcinomas showing distinctive clinicopathological features. In this study we investigated the rate of MSI and the correlation between MSI status and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
8
1
Order By: Relevance
“…The work presented here explored the prevalence of loss of MMR proteins in gastric cancer. The percentage (40%) of patients who revealed the loss of one or more MMR proteins is relatively high as compared to other studies demonstrating varying degree (5.6%-30%) of defective MMR expression all over the world in GC [15,16,18,22]. This observation suggests demographic and genetic factors prevailing in human populations contribute towards these variations.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The work presented here explored the prevalence of loss of MMR proteins in gastric cancer. The percentage (40%) of patients who revealed the loss of one or more MMR proteins is relatively high as compared to other studies demonstrating varying degree (5.6%-30%) of defective MMR expression all over the world in GC [15,16,18,22]. This observation suggests demographic and genetic factors prevailing in human populations contribute towards these variations.…”
Section: Discussionmentioning
confidence: 66%
“…Loss of MMR protein expression has been recorded in up to 30% of GC cases [14][15][16][17][18]. In the present study, we have reported the expression of four mismatch repair proteins, MLH1, MSH2, MSH6, and PMS2 in GC using an immunohistochemical staining procedure in Indian population along with the association of clinical parameters of GC patients with loss of expression of mismatch repair proteins.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…But, MSI positive tumours were more frequently located at the distal of the stomach and most of them were intestinal type by Laurén classifications and these observations are in line with previous study displayed MSI-H groups that represented loss of MMR proteins and associated with intestinal type. This also indicated its association with overall good prognosis (Karpinska-Kaczmarczyk et al, 2016). However, these data warrant a larger number of GCs samples for further evaluation to elucidate distinct prognosis between MSI tumours and clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…In this study, however determining affected MMR genes by IHC using MLH1 and MSH2 antibodies may lead to false negative MSI. It has been shown that PCR-based MSI detection was relatively low in GC, however higher prevalence of MLH1 and PMS2 were observed (Karpinska-Kaczmarczyk et al, 2016;Mathiak et al, 2017). Therefore, four antibodies panel (MLH1, MSH2, PMS2 and MSH6) are compulsory panel markers for further evaluation in order to increase sensitivity of IHC as predictive value that is almost equivalent to that of MSI analysis.…”
Section: Discussionmentioning
confidence: 99%